Structural evolution of aerogels prepared from TEOS sono-hydrolysis upon heat treatment up to 1100 degrees C - Vollet, D. R.; Donatti, D. A.; Ruiz, A. I.; de Castro, W. C. (Elsevier B.V., 2003)
The structural evolution of aerogels prepared from TEOS sono-hydrolysis was studied as a function of the temperature of heat treatment up to 1100 degreesC by means of small angle X-ray scattering (SAXS) and density measurements. The mass fractal structure of the original wet sonogel (with scattering exponent alpha similar to 2.2) apparently transforms to a surface fractal structure in a length scale lesser than similar to1.5 nm, upon the process resulting in aerogel. Such a structural transformation is interpreted by the formation of new particles with characteristic dimension of similar to1.5 nm, with rough boundaries or electronic density fluctuations (or ultra-micropores) in their interior. The structural arrangement of these particles seem to preserve part of mass fractal characteristics of the original wet sonogel, now in a length scale greater than similar to1.5 nm. The electronic density heterogeneities in the particles start to be eliminated at around 800 degreesC and, at 900 degreesC, the particles become perfectly homogeneous, so the structure can be described as a porous structure with a porosity of similar to68% with similar to9.0 nm mean size pores and similar to4.3 nm mean size solid particles. Above 900 degreesC, a vigorous viscous flux sintering process sets in, eliminating most of the porosity and increasing rapidly the bulk density in an aerogel-glass transformation. (C) 2003 Elsevier B.V. All rights reserved.